Proceso de enseñanza y aprendizaje en tiempos de pandemia del 2020, en escuela del municipio de Gachetá Cundinamarca, con niños y docentes de las Zonas Urbanas y Rurales (2021)
This research project was based on determining how the learning and teaching process has occurred in times of the 2020 pandemic, in the municipality of Gachetá Cundinamarca with students and teachers from rural and urban areas. For this, between two and three in-depth interviews were conducted with each teacher and student, a total of 4 teachers (two from each area) and 6 students (3 from each area) were interviewed.